Possible reduction of environmental impacts of geothermal energy extraction in a theoritical spa - Buday, Tamás (Acta Geographica Debrecina Landscape & Environment series, 2012)
Sustainable thermal water production involves the protection of the used reservoirs, as well as the minimizing of the environmental impact (caused by heat, gas and dissolved solid). Four water extraction models are discussed in which the water and heat demand of the theoretical spa are supplied using different sources. The most environmental friendly variation contains three wells with different depths of screening. In this case the dissolved gas and solid content became the lowest, as well as the radius of influence based on drawdown calculations. Beyond the environmental impact the owner have to consider other economic aspects, such as the number of wells, the possibility of independence from gas services, which force the owner to choose not the most environment friendly way. Optimizing the various factors, thermal water extraction for medical and wellness purposes could be feasible and appropriate for sustainable operation.